2007
DOI: 10.1111/j.1467-9566.2007.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Jumping off and being careful: children's strategies of risk management in everyday life

Abstract: This article addresses the complexity of children's risk landscapes through an ethnography of 10-to 12-year-old Danish children. The data revealed how children individually and collectively engaged with risk in their everyday activities. The children assessed risks in relation to their perceptions of their health as strength and control, negotiated the conditions of playing, and attuned their responses to situations of potential social and physical conflict. In the paper this risk engagement is illustrated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 23 publications
2
93
0
4
Order By: Relevance
“…That their own traffic risk management is often perceived to be so good it negates traffic risk is mirrored in other studies (Christensen and Mikkelsen, 2008;Green and Hart, 1998). One consequence is that if they are involved in a traffic incident, it is implicitly their own fault.…”
Section: Discussionmentioning
confidence: 91%
“…That their own traffic risk management is often perceived to be so good it negates traffic risk is mirrored in other studies (Christensen and Mikkelsen, 2008;Green and Hart, 1998). One consequence is that if they are involved in a traffic incident, it is implicitly their own fault.…”
Section: Discussionmentioning
confidence: 91%
“…10,11 From a young age, children seek risk when they play and use their judgment to assess risk and potential injury. 12,13 Children want risk; playgrounds are said to be "boring" if no risk is involved. 14 However, little research has examined the pros and cons of greater risk and challenge in play.…”
mentioning
confidence: 99%
“…Green (1997) found that physical risk taking is an important factor in the creation of boys’ social identity. Results of a recent ethnographic study suggest that girls are risk takers when social domains are included and that children’s risk engagement and risk taking are a balancing act between risk willingness and self-care within the context of social relationships, emotional excitement, and connections and activities with other children (Christensen & Mikkelsen, 2008). Possibly the intervention was not motivating enough to lower risk-taking behavior because it did not attend to the social identity and perceptions of other peers in the group.…”
Section: Discussionmentioning
confidence: 99%